2000
DOI: 10.1038/sj.bmt.1702640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complete response on outcome following autologous stem cell transplantation for myeloma

Abstract: Summary:We studied the effect of complete response (CR) among 126 consecutive patients who underwent stem cell transplantation (SCT) for myeloma. The CR rate with SCT was 33%. Median overall survival (OS) from diagnosis of myeloma was 56 months. OS following SCT was 22 months. Progression-free survival (PFS) was 12 months. OS was not different between patients who achieved CR and those who did not, median survival 25 vs 24 months, P = 0.5. Corresponding median times for PFS were 15 and 11 months, P = 0.2. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 26 publications
4
30
0
2
Order By: Relevance
“…There has been some evidence that achieving CR after ASCT does not result in prolonged PFS, 33 particularly in patients relapsing after, or who are refractory to standard chemotherapy. 34 However, our data confirm the results of several other studies showing that achieving CR has an important influence on PFS and that this subset of patients may derive the greatest benefit from the procedure. 10,35 Advanced age has been shown to be a poor prognostic factor in several trials using conventional chemotherapy [5][6][7] or ASCT.…”
Section: Asct In Multiple Myeloma E Terpos Et Alsupporting
confidence: 82%
“…There has been some evidence that achieving CR after ASCT does not result in prolonged PFS, 33 particularly in patients relapsing after, or who are refractory to standard chemotherapy. 34 However, our data confirm the results of several other studies showing that achieving CR has an important influence on PFS and that this subset of patients may derive the greatest benefit from the procedure. 10,35 Advanced age has been shown to be a poor prognostic factor in several trials using conventional chemotherapy [5][6][7] or ASCT.…”
Section: Asct In Multiple Myeloma E Terpos Et Alsupporting
confidence: 82%
“…Some authors also believe that better responses after transplant are associated with improved survival. 10,20,21 In contrast, Rajkumar et al 33 reported that the outcome following ASCT depends more on biological variables, such as plasma cell labelling index rather than on the CR status.…”
Section: Discussionmentioning
confidence: 95%
“…Achievement of a complete response is one of the strongest predictors of TTP after ASCT. 31,32 While long-term results with the new regimens such as Len-Dex appear to result in CR rates comparable to that of ASCT, the CR rates after four cycles of treatment, where a majority of patients go on to receive high-dose therapy is under 10% and far below the CR rates seen with transplant. 11 So it is quite conceivable that initial demonstrating the median overall survival from diagnosis among the groups of patients receiving different initial therapies for their disease.…”
Section: Discussionmentioning
confidence: 99%